Influence of cultivation conditions on antimicrobial properties of Nocardia vaccinii ІMV B-7405 surfactants - Pirog, Tatiana; Panasiuk, Catherine; Kliuchka (Nykytyuk), Lilia; Iutinska, Galina (My University, 2016)
The aim of the work was to study of antimicrobial effect of Nocardia vaccinii ІMV B-7405 surfactants, synthesized in various cultivation conditions, against phytopathogenic bacteria of genera Pseudomonas, Xanthomonas, and Pectobacterium. The antimicrobial properties of surfactants were determined in suspension culture by Koch method and also by index of the minimum inhibitory concentration. Surfactants were extracted from supernatant of cultural liquid using mixture of chloroform and methanol (2: 1). It has been established that antimicrobial properties of surfactants depend on the nature of the carbon source in the medium (refined sunflower oil, as well as waste oil after frying potatoes and meat, glycerol), the duration of the cultivation (5 and 7 days), the degree of surfactants purification (the supernatant of cultural liquid, purified surfactants solution) and the test culture type. The highest antimicrobial activity was exhibited by purified surfactants solutions synthesized by ІMV B-7405 strain on the waste oil after potato frying (decreased survival of pathogenic bacteria by 50–95%), and surfactants formed within 7 days of N. vaccinii ІMV B-7405 cultivation on all test substrates (minimum inhibitory concentration 7–40 μg/ml, which is several times lower than the surfactant, synthesized for 5 days). These data are promising for the development of ecologically friendly biopreparations to control the number of phytopathogenic bacteria.
Keywords: кафедра біотехнології і мікробіології; Nocardia vaccinii IMB В-7405; surfactants; поверхнево-активні речовини; поверхностно-активные вещества